High-throughput genotyping robot-assisted method for mutation detection in patients with hypertrophic cardiomyopathy. - Bortot, Barbara; Athanasakis, Emmanouil; Brun, Francesca; Rizzotti, Diego; Mestroni, Luisa; Sinagra, Gianfranco; Severini, Giovanni Maria (Diagn Mol Pathol, 2011)
Hypertrophic cardiomyopathy (HCM) is the most frequent autosomal dominant genetic heart muscle disease and the most common cause of sudden cardiac death in young people (under 30 y of age), who are often unaware of their underlying condition. Genetic screening is now considered a fundamental tool for clinical management of HCM families. However, the high genetic heterogeneity of HCM makes genetic screening very expensive. Here, we propose a new high-throughput genotyping method based on a HCM 96-well sequencing plate for the analysis of 8 of the most frequent HCM-causing sarcomeric genes by automating several processes required for direct sequencing, using a commercially available robotic systems and routinely used instruments. To assess the efficiency of the robot-assisted method, we have analyzed the entire coding sequence and flanking intronic sequences of the 8 sarcomeric genes in samples from 18 patients affected by HCM and their relatives, which revealed 9 different mutations, 3 of which were novel. The automated, robot-assisted assembling of polymerase chain reaction, purification of polymerase chain reaction products, and assembly of sequencing reactions resulted in a substantial saving of time, reagent costs, and reduction of human errors, and can therefore be proposed as a primary strategy for mutation identification in HCM genetic screening in many medical genetic laboratories.
Keywords: Cardiomyopathy, Hypertrophic; DNA Mutational Analysis; Genetic Predisposition to Disease; Genetic Testing; Genotyping Techniques; High-Throughput Nucleotide Sequencing; Humans; Muscle Proteins; Mutation; Robotics